2019
DOI: 10.1021/acs.macromol.9b01307
|View full text |Cite
|
Sign up to set email alerts
|

pH-Responsive Water-Soluble Cyclic Polymer

Abstract: Cyclic polymers possess different properties compared to their linear analogues of the same molecular weight, such as smaller hydrodynamic volumes and higher glass transition temperatures (T g ). Cyclic poly(4-ethynylanisole) (cPEA) was synthesized via a catalytic ring-expansion of 4-ethynylanisole. The catalyst employed was a tungsten complex supported by a tetraanionic pincer ligand. Evidence of the cyclic topology comes from gel permeation chromatography, dynamic light scattering, static light scattering, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 62 publications
(120 reference statements)
2
41
0
Order By: Relevance
“…A similar result was recently reported by Veige et al , who demonstrated that linear and cyclic polyphenols display nearly the same value of p K a when dissolved in aqueous media.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…A similar result was recently reported by Veige et al , who demonstrated that linear and cyclic polyphenols display nearly the same value of p K a when dissolved in aqueous media.…”
Section: Resultssupporting
confidence: 89%
“…Interestingly, a very similar, general trend was observed for the two different polymer topologies, for which a comparable pK a value between 6 and 6.5 was identified. 52,53 A similar result was recently reported by Veige et al, 54 who demonstrated that linear and cyclic polyphenols display nearly the same value of pK a when dissolved in aqueous media.…”
Section: Resultssupporting
confidence: 84%
“…Stimulus responsive polymers , have recently attracted more and more interest. They are able to respond to various stimuli like temperature, , pH, stress, , voltage, and light. Because the temperature can be easily controlled, thermoresponsive polymers are extensively studied. An aqueous thermoresponsive polymer solution presents an abrupt change of transmittance from transparent to turbid once the external temperature is above the transition temperature (TT). , This change is caused by the changed interactions between hydrophilic and hydrophobic groups in the polymer with the surrounding water upon heating.…”
Section: Introductionmentioning
confidence: 99%
“…Stimuli-responsive polymers have attracted significant attention because of their variation with the changes of physical and/or chemical properties by the introduction of various important stimuli, such as temperature, pH, light, and glucose. The implication of such a responsive polymer mostly relies on the controlled drug delivery application . However, their involvement in sensing applications is still in a premature state.…”
Section: Introductionmentioning
confidence: 99%